ANALISIS STRATEGI PEMASARAN UMKM BAKERY DALAM MENINGKATKAN VOLUME PENJUALAN - Nuriawati; Siti Aisyah; Jody Eriyanto (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study enriches the literature on MSME marketing by revealing the lack of application of the digital marketing mix in the small-scale bakery sector in rural areas. The objective is to determine the marketing strategy for increasing sales volume at Queenpai Bakery Store Paiton. The research method used qualitative research and field study. The research results indicate that the implementation of the marketing mix, specifically the 4Ps—Product, Price, Place, and Promotions is ineffective. In the digital age, many similar businesses have introduced their products to the market using the 4Ps effectively, leading to a significant decline in sales at the store. Promotions, is ineffective because in this digital era, many similar businesses have introduced their products to the market with the proper application of the 4Ps, resulting in a significant decline in sales at the store. Additionally, Queenpai Bakery Store needs to utilize social media as a platform for conducting sales activities, including product promotion, communicating the store’slocation, and product pricing.